2021
DOI: 10.1007/s13346-021-01007-3
|View full text |Cite|
|
Sign up to set email alerts
|

Chitosan-based hydrogels to treat hydrofluoric acid burns and prevent infection

Abstract: There is an urgent need for treatments for hydrofluoric acid (HF) burns and their derivative problems that prevent hydrogen ion dissociation and fluoride ion binding to tissues. This study evaluated the ability of chitosan-based hydrogels combined with a buffer solution containing either boric acid or Tris and calcium gluconate (CHS-BA-CG and CHS-Tris-CG) to repair HF burn wounds and prevent wound infections. We assessed calcium release rates and biocompatability and constructed a mouse HF burn model to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In the literature there is no chitosan hydrogel prepared by using NaBF 4 ; however, there are some studies investigating the synergetic effect of boron compounds with chitosan for their potential use as wound care applications. In a study conducted by Huang et al ( 2021) chitosanbased hydrogels were prepared by using boric acid or Tris and calcium gluconate containing buffer solutions [52]. According to the results both gels demonstrated tissue repair and anti-infection effects and they were evaluated as potential wound care material for hydrofluoric acid burn therapy.…”
Section: Agar Disk Diffusion Results Of Ch:nabf 4 Hydrogelsmentioning
confidence: 99%
“…In the literature there is no chitosan hydrogel prepared by using NaBF 4 ; however, there are some studies investigating the synergetic effect of boron compounds with chitosan for their potential use as wound care applications. In a study conducted by Huang et al ( 2021) chitosanbased hydrogels were prepared by using boric acid or Tris and calcium gluconate containing buffer solutions [52]. According to the results both gels demonstrated tissue repair and anti-infection effects and they were evaluated as potential wound care material for hydrofluoric acid burn therapy.…”
Section: Agar Disk Diffusion Results Of Ch:nabf 4 Hydrogelsmentioning
confidence: 99%
“… 31 , 32 A recent study indicated that chitosan‐based hydrogels alone can be used to treat hydrofluoric acid burns and prevent infection. 33 Similarly, chitosan‐based hydrogels act as thermo‐sensitive hydrogels for drug delivery. 34 The chitosan/calotropis procera‐based hydrogels were able to stimulate the formation of granulation tissue and angiogenesis in wound healing applications.…”
Section: Discussionmentioning
confidence: 99%
“…At present, many hydrogel dressing products made of natural or artificial polymer materials have been used in clinical applications, including AQUACEL, TegaGel, and NuGel 31,32 . A recent study indicated that chitosan‐based hydrogels alone can be used to treat hydrofluoric acid burns and prevent infection 33 . Similarly, chitosan‐based hydrogels act as thermo‐sensitive hydrogels for drug delivery 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Meng et al review the applications of chitosan-based systems for the treatment of infectious diseases, as well as the design considerations including adhesive ability, controlled release function, and other physical properties [27]. Skin application of chitosan-based hydrogels was reported by Huang et al [28]. Chitosan-based hydrogels showed improved recovery of hydrofluoric acid burns with the prevention of skin infections.…”
mentioning
confidence: 99%